Association of Checklist Use in Endotracheal Intubation With Clinically Important Outcomes: A Systematic Review and Meta-analysis - Turner, Joseph S.; Bucca, Antonino W.; Propst, Steven L.; Ellender, Timothy J.; Sarmiento, Elisa J.; Menard, Laura M.; Hunter, Benton R. (JAMA network open, 2020)
Endotracheal intubation of critically ill patients is a high-risk procedure. Checklists have been advocated to improve outcomes. To assess whether the available evidence supports an association of use of airway checklists with improved clinical outcomes in patients undergoing endotracheal intubation. For this systematic review and meta-analysis, PubMed (OVID), Embase, Cochrane, CINAHL, and SCOPUS were searched without limitations using the Medical Subject Heading terms and keywords airway; management; airway management; intubation, intratracheal; checklist; and quality improvement to identify studies published between January 1, 1960, and June 1, 2019. A supplementary search of the gray literature was performed, including conference abstracts and clinical trial registries. Full-text reviews were performed to determine final eligibility for inclusion. Included studies were randomized clinical trials or observational human studies that compared checklist use with any comparator for endotracheal intubation and assessed 1 of the predefined outcomes. Data extraction and quality assessment were performed using the Newcastle-Ottawa Scale for observational studies and Cochrane risk of bias tool for randomized clinical trials. Study results were meta-analyzed using a random-effects model. Reporting of this study follows the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) reporting guideline. The primary outcome was mortality. Secondary outcomes included first-pass success and known complications of endotracheal intubation, including esophageal intubation, hypoxia, hypotension, and cardiac arrest. The search identified 1649 unique citations of which 11 (3261 patients) met the inclusion criteria. One randomized clinical trial and 3 observational studies had a low risk of bias. Checklist use was not associated with decreased mortality (5 studies [2095 patients]; relative risk, 0.97; 95% CI, 0.80-1.18; I2 = 0%). Checklist use was associated with a decrease in hypoxic events (8 studies [3010 patients]; relative risk, 0.75; 95% CI, 0.59-0.95; I2 = 33%) but no other secondary outcomes. Studies with a low risk of bias did not demonstrate decreased hypoxia associated with checklist use. The findings suggest that use of airway checklists is not associated with improved clinical outcomes during and after endotracheal intubation, which may affect practitioners' decision to use checklists in this setting.